Sistema de treinamento em acuidade visual - SiTAV - Souza, Hudson Sérgio de (2014)
This dissertation describes the development of a web software, to provide visual acuity training to evaluators with or without experience in the process of evaluating incidence and severity of disease injure on plants in certain crops. Proper evaluator training process requires standard methods to quantify the plant disease injure area, pursuing to minimize subjectivity in estimating the severity of plant diseases, providing precision and accuracy training to evaluators. The severity variable is considered the best parameter to reference the damage caused by plant diseases on leaves or fruits, and diagrammatic scale is considered the best support alternative on lesions evaluation of plant diseases. The importance of proper visual acuity training is directly reflected in a collection of data that can efficiently determine the disease progress curve, used as standard to the most appropriate management for effective control of the disease in the field. The processing power of computing in everyday activities, repetitive, performing complex mathematical calculations and managing database, boosted both plant pathology and modern science, in advancing new scientific discoveries and immediate dissemination of the results. Export of training data from SiTAV project for to spreadsheet format (.xls) allowed the use of Statistic Analysis System (SAS) 9.3 statistical software to process the data and generate relevant information on evaluators performance and training quality of SiTAV system.